Cyanation and Hydrolysis Cascade of Aryl Bromides with Cuprous Cyanide to Access Primary Amides - Xia, Chunnian; Chen, Xiaolin; Dai, Jiawei; Gao, Feng; Wang, Ning; Wang, Junfeng; Xiao, Xiao; Dai, Fengli; Li, Yifang; Hong, Bo (Synlett, 2023)
A convenient and efficient approach for the cyanation and hydrolysis of aryl bromides to afford primary amides was developed, in which cuprous cyanide is used as a cyanide source and a catalyst. It has the advantages of excellent functional-group compatibility, medium to high yields, a one-pot procedure, and a non-noble-metal catalyst. The reaction could be performed on a gram scale to give N-allyl-N-methyl-5-nitroisophthalamide in a 73% yield.
Keywords: primary amides; aryl bromides; copper(I) cyanide; copper catalysis; one-pot reaction; late-stage modification